Neurosurgery medical robot Remebot for the treatment of 17 patients with hypertensive intracerebral hemorrhage. Issue 5 (25th July 2019) - Wang, Tao; Zhao, Quan‐Jun; Gu, Jian‐Wen; Shi, Tie‐Jun; Yuan, Xujun; Wang, Jia; Cui, Shao‐Jie
Abstract: Objective: To verify the minimally invasive surgical approach and therapeutic effects of using the medical neurosurgery robot Remebot to treat hypertensive intracerebral hemorrhage (HICH). Methods: Clinical data for 17 HICH patients were analyzed retrospectively. Hematoma evacuation and tube drainage using Remebot frameless stereotaxic techniques were performed for all patients, and urokinase was injected into the hematomas after the operations. Results: Robot‐assisted stereotactic techniques can accurately guide hematoma punctures, and no deaths occurred among these patients. The average positioning error was 1.28 ± 0.49 mm. The average drainage duration was 3.4 days. The 3‐month postoperative follow‐up revealed improved neurological functions and quality of life for all patients. Conclusions: The medical neurosurgery robot Remebot is minimally invasive, has high positional accuracy, and facilitates surgical planning according to the shape of the hematoma. Therefore, robot‐assisted surgery using Remebot represents a safe and effective treatment method for hematoma evacuation and tube drainage in HICH patients.